Pengaruh Pemberian Mikroorganisme Lokal (MOL) dari Bonggol Pisang terhadap Pertumbuhan dan Hasil Tanaman Bawang Putih Lokal Eban (Allium Sativum L.) - Deseriana Bria; Virginia Luruk Seran (Fakultas Pertanian, Universitas Timor, 2022)
This study aims to determine the effect of local microorganism (mol) on the growth and yield of garlic (Allium Sativum L.). The method used is a Randomized Block Design (RAK), namely Concentration (K) which consists of three levels, namely Control (No Treatment), Concentration 1:4 (K1), Concentration 1:5 (K2). The second factor is Watering Frequency (F) which consists of three levels, namely once every three weeks (F1), every five weeks (F2), and once every seven weeks (F3). The results of the study concluded that the 1:4 banana weevil mole concentration treatments were the best treatment in increasing the growth and yield of garlic plants. This can be seen from the highest value of the parameters of the number of leaves, fresh weight of tubers, dry weight of tubers, number of tubers per plant